The Role of Neurotropic B Vitamins in Nerve Regeneration. (14th July 2021) - Baltrusch, Simone
Abstract : Damage and regeneration naturally occur in the peripheral nervous system. The neurotropic B vitamins thiamine (B1), pyridoxine (B6), and cobalamin (B12) are key players, which maintain the neuronal viability in different ways. Firstly, they constantly protect nerves against damaging environmental influences. While vitamin B1 acts as a site-directed antioxidant, vitamin B6 balances nerve metabolism, and vitamin B12 maintains myelin sheaths. However, nerve injury occurs at times, because of an imbalance between protective factors and accumulating stress and noxae. This will result in the so-called Wallerian degeneration process. The presence of vitamins B1, B6, and B12 paves the way out to the following important regeneration by supporting the development of new cell structures. Furthermore, vitamin B1 facilitates the usage of carbohydrates for energy production, whereas vitamin B12 promotes nerve cell survival and remyelination. Absence of these vitamins will favor permanent nerve degeneration and pain, eventually leading to peripheral neuropathy.